Were-geeks save Wisconsin - Lyons, Kathy (Tallahassee, FL Dreamspinner Press, 2020)
"Chemist Josh Collier is having a blast at a comic book convention when he gets the shock of his life--he's a werewolf! WTF? Before he can howl, he's whisked away to a secret lair by a hot Roman centurion, Nero. Josh's former life is over, and his genius is needed at Wolf, Inc. Nero has no interest in babysitting a trainee were-geek when he'd rather be killing the demon that wiped out his entire pack. While Josh analyzes the monster's weapon, wild passion ignites between him and Nero. With destiny and their pack in the balance, can they survive the demon out to destroy Wisconsin?"--Goodreads.com
112552
Keywords: Werewolves -- Fiction; Shapeshifting -- Fiction; Gay men -- Fiction; Loups-garous -- Romans, nouvelles, etc; Metamorphose -- Romans, nouvelles, etc; Homosexuels masculins -- Romans, nouvelles, etc; Wisconsin -- Fiction; Paranormal romance stories; Romance fiction; Paranormal fiction; Gay fiction; Fiction; Romans homosexuels